Gambaran Kekumuhan di Kelurahan Mariso Kecamatan Mariso Kota Makassar - Mega Mustikasari (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2022)
Slum area is one of the problems which often discovered in big cities, particularly it appears and develops in strategic locations in the center of the city. With such phenomenon as slum, job, kinship, ethnic, religion and other social problems, then it can be said that the life condition of the people is heterogeneous. One of villages in Makassar city which experience social life problems related to slum area is Mariso village in Mariso Sub-district in Makassar City. The objectives of the research are Describe the slum in Mariso Village of Mariso Sub-District in Makassar City. The research employed descriptive approach systematically, factually, and accurately. The data were collected through interview and documentation study technique. The results of the research reveal that is slum in the area based on the variables which are measured in the location of the research. The description of slum in Mariso Village in RW 3 and RW 7 with the slum level is in medium category. It is because each of RW analyzed had the same slum variables.